PENGARUH TINGKAT KECUKUPAN DANA, UNDERWRITING, DAN RETENSI SENDIRI TERHADAP KINERJA KEUANGAN PERUSAHAAN ASURANSI TAHUN 2019-2022 - Adibaturrohmah, Adibaturrohmah; Safitri, Maria (Bisnis-Net, 2024)
Currently, insurance companies in Indonesia are experiencing rapid development. This encourages existing insurance companies to be able to meet the requirements related to finance. The purpose of this research is to determine the influence of the adequacy of funds, underwriting, dan self-retention on financial performance, proxied by return on assets, in insurance companies listed on the Indonesia Stock Exchange from 2019 to 2022. This research is conducted using a quantitative approach dan employs purposive sampling method. It also involves secondary data in the form of financial dan annual reports from 20 insurance companies obtained through documentation dan literature study techniques, which are then analyzed using a statistical approach through multiple regression analysis. The results of this study shown that the adequacy of funds dan self-retention have a positive dan significant impact on the financial performance of insurance companies. While, underwriting have a positive dan not significant effect on the financial performance of insurance companies.